2012
DOI: 10.1007/s00442-011-2212-9
|View full text |Cite
|
Sign up to set email alerts
|

Food for folivores: nutritional explanations linking diets to population density

Abstract: Ecologists want to explain why populations of animals are not evenly distributed across landscapes and often turn to nutritional explanations. In seeking to link population attributes with food quality, they often contrast nutritionally positive traits, such as the concentration of nitrogen, against negative ones, such as fibre concentration, by using a ratio of these traits. This specific ratio has attracted attention because it sometimes correlates with the biomass of colobine primates across sites in Asia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 53 publications
4
62
0
Order By: Relevance
“…This pattern is consistent with other studies in which it was found that monkeys of the genus Ateles are highly frugivorous to the degree that they are specialists (Di Fiore et al, 2008). Regarding the black howler monkeys, the results support the findings of other studies where A. pigra is considered mainly folivorous (which explains the high "Uf" proportion) (Wallis et al, 2012), but opposite to Garber et al (2015) who characterize this primate as one species with a balanced diet between leaves and fruits.…”
Section: Fruit Choicesupporting
confidence: 81%
“…This pattern is consistent with other studies in which it was found that monkeys of the genus Ateles are highly frugivorous to the degree that they are specialists (Di Fiore et al, 2008). Regarding the black howler monkeys, the results support the findings of other studies where A. pigra is considered mainly folivorous (which explains the high "Uf" proportion) (Wallis et al, 2012), but opposite to Garber et al (2015) who characterize this primate as one species with a balanced diet between leaves and fruits.…”
Section: Fruit Choicesupporting
confidence: 81%
“…In this regard Silver et al [2000] calculated the ratio as AP/ADF in leaves consumed by black howler monkeys in Belize, and also did not find differences between the protein-to-fiber ratio of young and mature leaves. This highlights the importance of measuring the amount of nutrients that can be digested and metabolized by the forager rather than the absolute amount of nutrients present in foods in understanding primate foraging decisions [DeGabriel et al, 2013;Wallis et al, 2012].…”
Section: Phytochemical Composition Of the Dietmentioning
confidence: 97%
“…The mechanism on how this parameter affects primate abundance remains unclear as this ratio may correlate with other leaf constituents that really drive the relationship . For example, Wallis et al (2012) suggests that the available nitrogen concentration of leaves, which covers both fiber and tannin content, is a real influencing factor on folivore leaf choice. More research is needed to determine why the protein-to-fiber index predicts folivore biomass.…”
Section: Previous Studies On Primate Abundancementioning
confidence: 99%